Investigating the system effect of reporting multidisciplinary care measures for cancer services in New South Wales, Australia - Kahren M. White; Ru K. Kwedza; Holly Seale; Reema Harrison (BMC, 2021)
Abstract Background Multidisciplinary cancer care to facilitate the provision of patient centred and evidence-based care is considered best practice internationally. In 2016 multidisciplinary care measures were developed for all local health districts across NSW. The aim of this study was to identify system-level changes and quality improvement activities across the NSW cancer system linked to reporting on these measures. Methods Focus group discussions were used to generate a synergy of ideas from key stakeholders. An exploratory descriptive approach was used within the ontological position of Framework Analysis, the analysis method chosen for this research study, sitting most closely within pragmatism. The use of Framework Analysis in the analytic strategy is because it is well-suited to addressing policy issues and maintaining specific focus within a wider dataset. Results Two focus groups were held with a total of 18 purposively selected participants. Four primary themes emerged: value of electronic documentation; role clarity; relationships; and future development of measures. Key findings included that the reporting of performance measures has expedited the development of electronic documentation and data extraction from the multidisciplinary team meeting (MDT), identified barriers and facilitators to MDT data collection and supported MDT improvement activities across NSW. Conclusions The findings of this study have highlighted that MDTs and their meetings across NSW are harnessing technological advancements to support and further develop their MDTs, as well as the challenges of implementing new processes within the MDTM. This study adds a unique contribution to knowledge of how the reporting of measures can assist in understanding variation in the development and implementation of multidisciplinary teams, as well as highlighting future programs of work to decrease variation in multidisciplinary team meetings and quality improvement activities.